Pemantauan Penyebaran Penyakit Demam Derdarah (DBD) Pada Kota Pagar Alam Berbasis Web Dengan Metode Waterfall - sasmita; Siti Muntari (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2020)
Dengue fever (DBD) is a contagious and dangerous disease. This is because the time of spread occurs in a short time and often causes outbreaks caused by dengue virus Changes in the state of the body condition for people with dengue fever occur very suddenly which is characterized by high fever, dizziness, bone and joint pain, pale face, and on the skin there is a red sign caused by a mosquito bite. This study aims to build a monitoring system for the spread of dengue fever (DBD) in the web-based City of Pagar in order to facilitate employees in carrying out their duties to provide information about the spread of dengue fever (DBD) and to find out the high and low dengue cases in Sidorejo puskesmas look for Dengue Fever (DBD) case data by year. The method used in the research is the Waterfall method, the Waterfall method provides a sequential or sequential software lifecycle approach starting from analysis, design, coding, testing. The results of this study can be used to monitor the spread of web-based dengue fever (DBD) in Pagar Alam City.